Clinical chorioamnionitis at term I: microbiology of the amniotic cavity using cultivation and molecular techniques - Romero, Roberto (J Perinat Med, 2015)
INTRODUCTION: The objectives of this study were: 1) to determine the amniotic fluid (AF) microbiology of patients with the diagnosis of clinical chorioamnionitis at term using both cultivation and molecular techniques; and 2) to examine the relationship between intra-amniotic inflammation with and without microorganisms and placental lesions consistent with acute AF infection. METHODS: The AF samples obtained by transabdominal amniocentesis from 46 women with clinical signs of chorioamnionitis at term were analyzed using cultivation techniques (for aerobic and anerobic bacteria as well as genital mycoplasmas) and broad-range polymerase chain reaction (PCR) coupled with electrospray ionization mass spectrometry (PCR/ESI-MS). The frequency of microbial invasion of the amniotic cavity (MIAC), intra-amniotic inflammation [defined as an AF interleukin 6 (IL-6) concentration ≥ 2.6ng/mL], and placental lesions consistent with acute AF infection (acute histologic chorioamnionitis and/or acute funisitis) were examined according to the results of AF cultivation and PCR/ESI-MS as well as AF IL-6 concentrations. RESULTS: 1) Culture identified bacteria in AF from 46% (21/46) of the participants, whereas PCR/ESI-MS was positive formicroorganisms in 59% (27/46) – combining these two tests, microorganisms were detected in 61% (28/46) of patients with clinical chorioamnionitis at term. Eight patients had discordant test results; one had a positive culture and negative PCR/ESI-MS result, whereas seven patients had positive PCR/ESI-MS results and negative cultures. 2) Ureaplasma urealyticum (n = 8) and Gardnerella vaginalis (n = 10) were the microorganisms most frequently identified by cultivation and PCR/ESI-MS, respectively. 3) When combining the results of AF culture, PCR/ESI-MS and AF IL-6 concentrations, 15% (7/46) of patients did not have intra-amniotic inflammation or infection, 6.5% (3/46) had only MIAC, 54% (25/46) had microbial-associated intra-amniotic inflammation, and 24% (11/46) had intra-amniotic inflammation without detectable microorganisms. 4) Placental lesions consistent with acute AF infection were significantly more frequent in patients with microbial-associated intra-amniotic inflammation than in those without intra-amniotic inflammation [70.8% (17/24) vs. 28.6% (2/7); P = 0.04]. CONCLUSION: Microorganisms in the AF were identified in 61% of patients with clinical chorioamnionitis at term; 54% had microbial-associated intra-amniotic inflammation, whereas 24% had intra-amniotic inflammation without detectable microorganisms.